2018
DOI: 10.1111/ijn.12717
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress experiences of nurses caring for cancer patients

Abstract: Aim The aim of this study was to explore secondary traumatic stress experiences of nurses caring for cancer patients. Methods A qualitative descriptive approach was taken in the study. The team conducted semi‐structured in‐depth interviews with 13 oncology nurses. We evaluated the responses collected using content analysis. Results Three distinct themes emerged from the interviews: cycle of desperation, coping, and change. Conclusion Based on the results obtained, it is suggested that programs containing cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…In other words, the impact of daily work stressors in ICUs is greater among those professionals with low dispositional harmonious passion compared to those with high dispositional harmonious passion, as they experience a large increase in shattered assumptions. This fact supports Lavigne and colleagues' (2014) theory, in which harmonious passion may change the perception of work stressors as the work setting is considered to be a positive and purposeful context and thus diminishes the impact on professionals' health, having a buffering effect (Peters, 2018).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In other words, the impact of daily work stressors in ICUs is greater among those professionals with low dispositional harmonious passion compared to those with high dispositional harmonious passion, as they experience a large increase in shattered assumptions. This fact supports Lavigne and colleagues' (2014) theory, in which harmonious passion may change the perception of work stressors as the work setting is considered to be a positive and purposeful context and thus diminishes the impact on professionals' health, having a buffering effect (Peters, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Firstly, we found compassion fatigue to be the emotional part of STS. Compassion fatigue was introduced as an explanation for nurses' burnout (Steinheiser, 2018) and is defined as a state of emotional exhaustion resulting from continued exposure to compassion stress (Jakimowicz et al, 2018); it may also result from the combination of trauma outcomes and the duty of empathetic caring (Mason et al, 2014), which is remarkably prevalent in intensive care settings (Peters, 2018). Moreover, daily work stressors in health professions have been established as a trigger for compassion fatigue in nurses (Yoder, 2010); therefore, the diary approach for deepening our understanding of the direct influence of daily work stressors on daily levels of compassion fatigue is supported.…”
Section: Secondary Traumatic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of STS has been reported frequently in many caring professions including nursing. There are several published studies examining STS and closely related conditions in different nursing specialties such as emergency care (7)(8)(9), critical care (10), cancer/oncology (11,12), internal medicine/heart and vascular nurses (13), primary care (14), labor and delivery (15), psychiatric care (16), and pediatric care (17,18). These studies demonstrated that STS is a frequent condition across nursing specialties, with prevalence rates ranging between 35% and 60% (19).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies showed that stress is related to or affects STS and CS [16][17][18]. In addition, positive (CS) or negative (STS) feelings experienced by nurses may affect burnout [19,20].…”
Section: Introductionmentioning
confidence: 99%